The careers of graduates of special schools – different faces of adulthood among people with mild intellectual disabilities - KAISER, IZABELLA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Izabella Kaiser, The careers of graduates of special schools – different faces of adulthood among people with mild intellectual disabilities. Interdisciplinary Contexts of Special Pedagogy, no. 25, Poznań 2019. Pp. 255-273. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2019.25.11 The source literature lacks a precise vision of an adult with an intellectual disability. The dominant view, in which the life of people with intellectual disabilities is perceived, is the indication of health, architectonic, employment, and educational barriers, or of the lowered social competencies required for the proper fulfilment of social roles. Is that right? The fates of the graduates of one of the special schools in Poznań, are an attempt to answer that. The subjects include both professionally active and unemployed graduates, women who have established families, and fulfil the roles mothers and wives, as well as, an adult man receiving pension benefits. The stories of Justyna, Patryk, Ania and Kamil, prove that people with mild intellectual disabilities consider vocational work as one of the basic attributes of adulthood. Simultaneously, they imply the need for urgent changes in special vocational education, aimed at minimising the observed discrepancies between the vocational competencies acquired by people with disabilities, and their fitness regarding the modern labour market. The fates of two adult women, Beata and Magda, confirm that marriage and family are values held in high regard, remaining an important aspect in the life plans of people with intellectual disabilities. Szymon’s story is an example of a man who, due to somatic disorders accompanying intellectual disabilities, and the overprotective attitude of his parents, is unable to act as a fully mature person. Therefore, the adulthood of persons with mild intellectual disabilities has many faces. It seems important to monitor the situation of special school graduates systematically, as, in the constantly changing reality, it will allow them, to be more rationally prepared for the fulfilment of their social life.